2018
DOI: 10.4103/ijd.ijd_565_17
|View full text |Cite
|
Sign up to set email alerts
|

Factors aggravating or precipitating acne in Indian adults: A hospital-based study of 110 cases

Abstract: Background:Although acne is principally a disorder of adolescence, the number of adult patients with acne is increasing. Adult acne is defined as the presence of acne beyond the age of 25 years. There is relatively few data on the prevalence and studies of acne in adult population.Aim and Objectives:To analyze the various factors that aggravate or precipitate acne vulgaris in Indian adults.Materials and methods:The study was done at the Department of Dermatology at a tertiary care center in Kerala for a period… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 13 publications
2
18
1
Order By: Relevance
“…Dreno et al indicated individuals with acne suffered from significantly higher stress levels than in acne-free individuals ( 28 ). Epidemiological surveys in Japan ( 77 ), India ( 80 ), and South Korea ( 76 ) all found that stress was an aggravating factor for the cause of acne.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Dreno et al indicated individuals with acne suffered from significantly higher stress levels than in acne-free individuals ( 28 ). Epidemiological surveys in Japan ( 77 ), India ( 80 ), and South Korea ( 76 ) all found that stress was an aggravating factor for the cause of acne.…”
Section: Resultsmentioning
confidence: 99%
“…Sun exposure played a significant role in the incidence of acne. A survey of acne patients in India showed that 26.4% of them developed skin lesions after exposure to sunlight and seasonal variation was observed in 44.5% patients exacerbated, because of increased amount of sunshine exposure in summer months ( 80 ). Dreno et al found acne was significantly more frequent in individuals with moderate or intensive sun exposure due to their work or daily activities ( 28 ).…”
Section: Resultsmentioning
confidence: 99%
“…It has been historically believed that low-grade persistent acne in females could occur majorly due to cosmetics use which lead to the use of the term “acne cosmetica” coined by Kligman. [ 24 ] A hospital-based study noted that 40% of adult acne patients experienced an aggravation of lesions after cosmetic use[ 21 ] which was supported by another study, which also concurred that a statistically significant difference in acne severity between “make-up” users and nonusers was seen. [ 18 ] Significantly, females with persistent acne were found to have a higher use of foundation.…”
Section: Discussionmentioning
confidence: 77%
“…also observed that oily foods and dairy products precipitated acne in 37.3% and 1.8% adult acne patients, respectively. [ 21 ] Diet has been propounded to cause acne via deranged nutrient signaling-induced hyperkeratosis and hyperseborrhea. [ 22 23 ] This with over-activation of mTORC1 by a high glycemic dietcan cause acne in conjunction with increased levels of androgens.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] Genetic predisposition, anxiety and depression, hyperglycemic diet, sunlight or artificial light, are additional factors known to be involved in the pathogenesis of acne. 4 Acne is clinically characterized by different clinical aspects and severity, spanning from mild forms, mainly characterized by retentional lesions (RTL) (open and closed comedones) with or without few inflammatory lesions (IFL) (papules/ pustules), to moderate or severe forms, with multiple IFL that seriously impact on patient's quality of life. 5,6 The treatment vary according to disease severity.…”
Section: Introductionmentioning
confidence: 99%